Vincent Scully Detonates the Past - Eeva-Liisa Pelkonen (Joelho, 2022)
The essay discusses the role which art historian Vincent Scully (1920‑2017) played in revisioning modern architecture’s relationship to time and history. The focus is on the psychoanalytical turn in his scholarship, which dictated that architecture was a product of collective memories rather than of historical processes. It makes a larger argument that art history, since Freud introduced the idea of “unconscious” architectural history, often became written from the perspective and for the benefit of the present.